Aicardi Syndrome: Key Fetal MRI Features and Prenatal Differential Diagnosis - Masnada, Silvia; Chiara, Doneda; Giana, Izzo; Manuela, Formica; Marco, Scarabello; Andrea, Accogli; Patrizia, Accorsi; Nadia, Bahi-Buisson; Valeria, Capra; Mara, Cavallin; Bernardo, Dalla Bernardina; Francesca, Darra; Valentina, De Giorgis; Elisa, Fazzi; Miguel, Fontanillas R. L.; Carlo, Fusco; Lucio, Giordano; Simona, Orcesi; Lorenzo, Pinelli; Erika, Rebessi; Antonino, Romeo; Mariasavina, Severino; Carlotta, Spagnoli; Pierangelo, Veggiotti; Anna, Pichiecchio; Andrea, Righini; Cecilia, Parazzini (Neuropediatrics, 2020)
Objective This study was aimed to investigate the prenatal findings in Aicardi syndrome (AIC) by intrauterine magnetic resonance imaging (iuMRI) suggesting possible diagnostic criteria and differential diagnosis.Methods The iuMRI features of nine AIC confirmed cases were described and then compared with those of postnatal MRI. Furthermore, all iuMRI cases with both corpus callosum (CC) agenesis–dysgenesis and cortical malformation (AIC mimickers) were retrospectively reviewed and compared with iuMRI AIC cases, in order to identify possible neuroradiological predictors of AIC syndrome. For this purpose, Chi-square statistic and binary logistic regression analysis were performed.Results In all AIC cases, iuMRI was able to detect CC agenesis–dysgenesis and cortical development anomalies. Postnatal MRI revealed some additional findings mainly including further cystic lesions and in two cases small coloboma. A statistically significant difference between AIC and AIC mimicker were found regarding sex, nodular heterotopias, posterior fossa abnormalities, coloboma, and cortical gyration abnormalities. The most predictive variables in the logistic regression model were cortical gyration abnormalities, coloboma, and sex.Conclusion The iuMRI findings may suggest prenatal diagnosis of AIC syndrome with significant impact on parental counseling. Among possible differential diagnoses, tubulinopathies emerged.
Keywords: Aicardi syndrome; prenatal suspicious; differential diagnosis